Interpretation of the mucous plug through sialendoscopy. (13th February 2021) - Fusconi, Massimo; Meliante, Piero G.; Pagliuca, Giulio; Greco, Antonio; de Vincentiis, Marco; Polimeni, Antonella; Musy, Isotta; Candelori, Francesca; Gallo, Andrea
Abstract: Objective: The purpose of this manuscript is to highlight the behaviour of mucus inside the ducts of the major salivary glands, in presence of typical pathologies, through images obtained with sialendoscopy. Subject: The authors present and comment on some sialendoscopies that show mucous plug in the ducts of the major salivary glands. Results: In primary Sjogren's syndrome, mucous plugs confirm the qualitative anomaly of the mucins and acidification saliva. Instead, salivary calculations behave like foreign bodies that generate mechanical pressure and friction on the duct walls of major salivary glands, so mucus deposits in the duct in its defence; in case of infected stone, mucous plugs are formed also with the function of protecting the ducts from the aggression of germs. During sialadenitis, there is a conflict between mucus and bacteria which explains sialendoscopic evidence such as white duct walls and mucous plugs. Conclusions: The study of the salivary ducts through sialendoscopy often confirms the clinical diagnosis or hypothesize it. During its execution, it is necessary not only to liberate the ducts of the major salivary glands but also analyse the appearance of the mucous plugs and the ductal walls as they are useful to guide the physician towards diagnosis.